Pengalaman Peternak Ayam Broiler Dalam Menjalankan Usaha Dengan Sistem Kemitraan Dan Mandiri: Studi Kasus Di Kabupaten Bulukumba - Rayyani, Wa Ode; Andriani, Sri (CV.ITTC INDONESIA, 2025)
This study aims to explore the experiences of broiler chicken farmers in running a business with a partnership and independent system in Bulukumba Regency. The method used in this study is a qualitative approach with a case study design, which involves in-depth interviews with broiler chicken farmers who apply both systems. The results of the study indicate that farmers who use a partnership system tend to feel greater support from partners, including in terms of access to capital, training, and product marketing. However, they also face challenges related to dependence on partners and profit sharing that is not always fair. On the other hand, farmers who run their businesses independently have the freedom to make decisions and manage their businesses, but often face difficulties in terms of access to resources and markets. These findings provide important insights into the dynamics faced by broiler chicken farmers in Bulukumba Regency, as well as implications for the development of policies and practices in the livestock sector. This study is expected to be a reference for farmers, academics, and stakeholders in improving the sustainability of broiler chicken farming businesses in the area.